Mesh free model of nanobeam integrated with a flexoelectric actuator layer. (1st January 2017) - Ray, M.C.
Abstract: This paper is concerned with the development of a mesh free model for the static analysis of smart nanobeams. The top surface of the substrate nanobeam is integrated with a flexoelectric layer which acts as the distributed actuator of the nanobeam. A layer wise displacement theory has been used to derive the model. Both thick and thin substrate nanobeams are considered for presenting the numerical results. The responses of the smart nanobeams computed by the present new mesh free model based on the layer wise displacement theory excellently match with those obtained by the exact solutions. The performance of the active flexoelectric layer either as an axial or as a shear actuator has been investigated. Variation of the control authority of the active flexoelectric layer with its thickness has also been investigated. The model derived here suggests that the mesh free method can be efficiently used for the numerical analysis of smart nanostructures coupled with flexoelectric actuator layer.